Hakikat Guru dalam Mengembangkan Nilai Agama dan Moral pada Anak Usia Dini: The Nature of Teachers in Developing Religious and Moral Values in Early Childhood - Nurul Hidayah Hadianti Putri; Astuti Darmiyanti; Nida’ul Munafiah (Universitas Ngudi Waluyo, 2024)
This study focuses on the nature of teachers in developing religious and moral values ​​in early childhood. The purpose of the study is that researchers want to know how a teacher develops religious and moral values ​​in Al-Anhar Karawang Kindergarten (TK). The method used is a qualitative method with a descriptive approach. The data collection method is carried out by direct observation and interviews, the participants involved are children aged 4-5 years, teachers and principals. The results of the study show that children aged 4-5 years in Al-Anhar Kindergarten have mostly achieved the target in developing religious and moral values, namely by showing several understandings and activities that are applied both at school and at home, one of which is by reading daily prayers. ABSTRAK Penelitian ini berfokus pada hakikat guru dalam mengembangkan nilai agama dan moral pada anak usia dini. Tujuan penelitian adalah peneliti ingin mengetahui bagaimana cara seorang guru dalam mengembangkan nilai agama dan moral di taman kanak-kanak (TK) Al-Anhar Karawang. Metode yang digunakan adalah metode kualitatif dengan pendekatan deskriptif. Metode pengumpulan data dilakukan dengan Pengamatan dan wawancara langsung, partisipan yang terlibat adalah anak usia 4-5 tahun, guru dan kepala sekolah. Hasil penelitian menujukkan bahwa anak usia 4-5 tahun di TK al-Anhar sebagaian besar telah mencapai target dalam mengembangkan nilai agama dan moral yaitu dengan ditunjukkan beberapa pemahaman dan kegiatan yang diterapkan baik di sekolah maupun dirumah, salah satunya dengan membaca doa sehari-hari.